The fighter force - Ansar Ali Majeth (Tentera Udara Diraja Malaysia, Menteri Pertahanan, 2013)
This book is intended to pay tribute to the pioneers and veterans of the RMAF fighter force, for their contributions, efforts and sacrifices in moulding the fighter force into what it is today. Hope this book will inspire as well enlighten both members of the RMAF and the general public. Additionally, it should even motivate young and vibrant Malaysians to join the RMAF, particularly the elite fighter force. Finally, this book should also serve as an official history of the fighter force and a convenient source of information for those interested in the combat capability of the RMAF